Development of cellulose acetate-chitosan-metal organic framework forward osmosis membrane for recovery of water and nutrients from wastewater. Issue 5 (October 2021) - Lakra, Reshma; Balakrishnan, Malini; Basu, Subhankar
Abstract: Aluminium fumarate (AlFu) metal organic framework (MOF) incorporating forward osmosis (FO) membrane prepared by coating chitosan (CS)-AlFu MOF mix on cellulose acetate (CA) membrane. AlFu MOF in the membrane separation layer enhanced hydrophilicity and resulted in higher water flux and lower reverse salt flux than CA or the CA-CS membranes. The M-1–0.06 membrane with 1% CS coating and 0.06 wt% AlFu MOF addition identified to be optimal. Using MgCl2 .6 H2 O as the draw, the membranes tested for concentration of nutrients from synthetic wastewater (SW) and real wastewater (RW) from a cowshed. For the SW feed, M-1–0.06 displayed enhanced water flux (18 LMH compared to 11.8 LMH for CA membrane) and accumulation (concentration) of components as follows: COD (2X), NH4 -N (1.9X), NO3 -N (0.76X) and PO4 (0.85X). With RW feed, the water flux was lower (8.75 LMH), but components concentration was higher: COD (3.75X), NH4 -N (4.46X), NO3 -N (3.35X) and PO4 (5.1X). Fouling due to cake layer deposits on the membrane surface could be removed by physical cleaning. Over 80% water recovery obtained in FO, and 85% salt rejection was obtained from diluted draw solution using reverse osmosis (RO). The nutrients in concentrated feed wastewater recovered as struvite (NH4 MgPO4 .6 H2 O) by precipitating, using the RO reject, which was also the re-concentrated draw solution for the next FO experiment. Graphical Abstract: Graphical abstract of the wastewater treatment process ga1 Highlights: Cellulose acetate FO membrane coated with chitosan-AlFu MOF mix was prepared. The surface coating enhanced membrane hydrophilicity and increased water flux. FO-RO concentrated nutrients in wastewater and recovered water from diluted draw. Struvite was precipitated from concentrated nutrients using reconcentrated draw.